A bone remodeling model governed by cellular micromechanics and physiologically based pharmacokinetics. (April 2020) - Bahia, M.T.; Hecke, M.B.; Mercuri, E.G.F.; Pinheiro, M.M.
Abstract: This study describes a mathematical model for bone remodeling that integrates the bone cells activities with the pharmacological dynamics for bone-seeking agents. The evolution of bone cells population involves the osteoblast-osteoclast signaling mediated by biochemical factors and receives both mechanical stimulus evaluated at the microscale and pharmacological regulation. A physiologically based pharmacokinetic model (PBPK) for bone-seeking agents was developed to provide the drug concentration on bone sites and feed the remodeling algorithm. The drug effect on bone was reproduced coupling three different strategies: modification of the RANKL expression, increase the osteoclast apoptosis and change in the rate of differentiation of preosteoblasts. Computational simulations were performed in the PBPK model considering different dosing regimens. A 3D finite element model of a proximal femur was generated and the simulation of the bone remodeling algorithm were implemented in Matlab. The results indicate that the proposed integrated model is able to capture adequately the expected adaptive behavior of bone subjected to mechanical and pharmacological stimulus. The model demonstrated to have potential for use as a platform to investigate therapies and may help in the study of new drugs for bone diseases. Highlights: Cellular micromechanics and pharmacokinetics integrated in a bone remodeling model. Drug concentration at bone sites alters the dynamics of bone cell populations. Osteoporosis and its treatment simulated in a mechanobiologic model. Physiologically based pharmacokinetics model for bone seeking agents. Bone tissue modeled by a permeability rate limited tissue compartment model.